The Elderly Alzheimer Patient's Portable Tools for Position Detection with SMS Notifications - Yulastri, Yulastri; Madona, Era; Nasution, Anggara; Irmansyah, M. (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2021)
In this study, we propose a portable tool to monitor and monitor patients at risk of Alzheimer's. The aim of this research was to design and make a useful tool to determine the position and condition of Alzheimer's sufferers. The research stages consisted of designing hardware, software and testing the whole tool. The patient's condition find out by an accelerometer sensor was used which read the values of the x, y, and z axes to determine the condition of the patient normal or falling. This tool also has a panic button which is used by the patient if he does not know his position and forget the way to go home, and SMS notification will be sent to the colleague when this button is pressed. The results of the test show the device can send an SMS notification of the patient's position when the supervisor sends an SMS